Analysis of the German Compassionate Use Program on spesolimab in patients with generalized pustular psoriasis: evidence outside of clinical trials - Krefting, Frederik; Welzel, Julia; Thamm, Janis; Thölken, Karisa; Wohlrab, Johannes; Müller, Valentina Laura; Kreuter, Alexander; Rueff, Franziska; Sticherling, Michael; Hölsken, Stefanie; Placke, Jan Malte; Sondermann, Wiebke (European Journal of Dermatology, 2024)
Background: Generalized pustular psoriasis (GPP) is a potentially life-threatening orphan disease. Interleukin (IL)-36 is a known pathogenetic key driver of GPP. The IL-36 receptor inhibitor spesolimab has shown efficacy and safety in clinical trials. However, evidence for spesolimab outside of clinical trials is limited. Objectives: To provide additional evidence for the use of spesolimab beyond clinical trials, we evaluated individual patient data as part of the spesolimab Compassionate Use Program (CUP) for GPP patients in Germany. Materials & Methods: Adult patients with an acute GPP flare received 900 mg spesolimab intravenously at baseline and received a second dose on day 8. Data on demographics, efficacy and adverse events were collected from participating sites at baseline, on day 8 and at four weeks. Results: The database included datasets from 12 GPP patients. At baseline, 72% of patients with complete data regarding efficacy (n=7) had a GPPGA (Generalized Pustular Psoriasis Physician Global Assessment) of ≥3, and all patients a PS (pustulation subscore) of ≥3. On day 8, 43% of patients had a GPPGA ≤1 and 72% a PS ≤1. After four weeks, all patients had a GPPGA ≤1 and 86% a PS ≤1. No drug-related adverse events were reported. Conclusion: These findings confirm the results of international, randomized clinical trials in a real-world setting. As spesolimab is no longer available in Germany, this study provides important information that cannot be replicated in this country.
CRIS-Team Scopus Importer:2025-04-01
Keywords: Generalized pustular psoriasis; spesolimab